"[It's] more than just medicine": The value and sustainability of mandatory, non-clinical, short-term rural placements in a Western Australian medical school. (3rd May 2020) - Vujcich, Daniel L.; Toussaint, Sandy; Mak, Donna B.
Abstract: Introduction: In 2005, the University of Notre Dame School of Medicine (Western Australia) established a mandatory, non-clinical rural and remote (hereafter termed rural) health placement program delivered in 2 weeks over 2 years, largely resourced by voluntary human capital. Our study investigated whether the program: (1) encouraged medical graduates to seek rural employment; (2) enhanced their ability to meet rural people's health needs; and (3) was sustainable. Methods: A qualitative descriptive study collected data using semi-structured, in-depth interviews with graduates and placement hosts. Data were transcribed, coded and analysed using Framework Analysis to identify key themes. Results: Twenty-eight medical graduates and 15 community hosts participated. The program validated pre-existing interest in, or positively influenced graduates' attitudes towards, rural practice, and enabled empathy and responsiveness when caring for rural patients in urban, as well as rural, health services. Placement hosts unanimously supported the program and contributed social capital, to ensure its sustainability. Discussion: The program influenced a broad spectrum of students over 15 years and reflects a socially-accountable approach to medical education. Conclusions : This study demonstrates the sustainability and value of mandatory short-term community-based placements in improving medical graduates' responsiveness to the health needs of rural Australians.